(untitled) (Journal of Informatics Education and Research, 2024)
The effect of justice in organizations on staff engagement and well-being is examined in this research. The study used two questionnaires and discovered a favourable relationship between staff engagement, well-being, and organizational justice characteristics. Three aspects of organizational justice were also found by the research: distributive justice, interactional justice, and procedural justice. The impact of justice in the organization on staff engagement and happiness is being investigated empirically for the first time with this research. Managers should enhance fairness in the organization, provide rewards equally, and guarantee equitable promotion procedures for more senior positions, according to the research’s recommendations.